Gendered Space‐Time Constraints, Activity Participation and Household Structure: A Case Study Using A GPS‐Based Activity Survey in Suburban Beijing, China. (19th November 2015) - Ta, Na; Kwan, Mei‐Po; Chai, Yanwei; Liu, Zhilin
Abstract: Space‐time constraints imposed by employment and household responsibilities may lead to greater gender differences in individuals' participation in daily activities. However, few studies have directly examined the impact of household structure on the gender differences in space‐time constraints associated with various daily activities due to the lack of accurate space‐time data. Using a 7‐day GPS‐based activity‐travel diary dataset collected in Beijing, this paper investigates how household structure influences men's and women's space‐time constraints and reduces the related gender differences in daily activity participation. The results suggest that gender and household structure matters. Getting help from retired parents reduces the level of fixity household heads perceive and decreases gender differences in space‐time constraints. However, the degree of the impact differs among activities and retired parents' age, and fixity level depends on the individual and household background of the person initiating the activity.